Symmetry energy effects on isovector properties of neutron rich nuclei with Thomas-Fermi approach - Papazoglou, M. C.; Moustakidis, Ch. C. (HNPS Advances in Nuclear Physics, 2019)
At the present study we employ a variational method, in the framework of the Thomas-Fermi approximation, to study the effect of the symmetry energy on several isovector properties of various neutron rich nuclei. The motivation of the present work is twofold. Firstly we tried to construct a self-consistent and easily applicable density functional method to study the effect of the symmetry energy on the isovector structure properties of medium and heavy neutron rich nuclei. Secondly, our aim is, if it is possible, to combine our theoretical estimation with the relevant experimental or empirical data in order to suggest constraints on the density dependence of the symmetry energy for densities close to those of the interior of finite nuclei. According to the results, we confirm the strong dependence of the symmetry energy on the various isovector properties for the relevant nuclei, using possible constraints between the slope and the value of the symmetry energy at the saturation density.